Myeloid-Derived Suppressor Cells as Therapeutic Target in Hematological Malignancies - De Veirman, Kim; Van Valckenborgh, Els; Lahmar, Qods; Geeraerts, Xenia; De Bruyne, Elke; Menu, Eline; Van Riet, Ivan; Vanderkerken, Karin; Van Ginderachter, Jo A. (Frontiers in Oncology, 2014)
Myeloid-derived suppressor cells (MDSC) are a heterogeneous population of immature myeloid cells that accumulate during pathological conditions such as cancer and are associated with a poor clinical outcome. MDSC expansion hampers the host anti-tumor immune response by inhibition of T cell proliferation, cytokine secretion, and recruitment of regulatory T cells. In addition, MDSC exert non-immunological functions including the promotion of angiogenesis, tumor invasion, and metastasis. Recent years, MDSC are considered as a potential target in solid tumors and hematological malignancies to enhance the effects of currently used immune modulating agents. This review focuses on the characteristics, distribution, functions, cell–cell interactions, and targeting of MDSC in hematological malignancies including multiple myeloma, lymphoma, and leukemia.